A retrospective study on periparturient disorders in crossbred cows at organized farms in Uttar Pradesh - SINGH, RAJEEV; SHANKAR, HARRI; ARORA, B M (The Indian Journal of Animal Reproduction, 2023)
The prevalence of dystokia, stillbirths, abortions, retention of foetal membranes, prolapse of uterus and metritis wereascertained at organized farms of Bareilly and Allahabad Districts of Uttar Pradesh, during the period September I st, I 995 to August3 I, 1999. The prevalence of dystokia, stillbirths, abortions, retention of foetal membranes, prolapse of uterus and metritis were0.84, 4.60, 3.68, 15.22, 0.92 and 18.14 per cent respectively at Bareilly and 4.86, 5.24, 4.61 , 23.32, 2.12 and 33.42 per centrespectively, at Allahabad. The highest pre\'alence of dystokia, abortions, retention of foetal membranes were observed in summerseason (1.41, 4.58, 18.66 and 6.42, 9.63, 32.09 per cent) and still births in rainy season (9.72 and 7.41 per cent) at both farms ofBareilly and Allahabad, respectively. The metritis was common in rainy season at Bareilly (23 .96) and summer (42.25) at Allahabad.
Keywords: Reproductive disorders; organized farms; crossbred; retrospective study